2022
DOI: 10.1200/op.21.00883
|View full text |Cite
|
Sign up to set email alerts
|

National Survey on the Effect of Oncology Drug Shortages in Clinical Practice: A Hematology Oncology Pharmacy Association Survey

Abstract: PURPOSE: Drug shortages are a clear and growing challenge. Prominent shortages included oncology medications and supportive care products essential for the care of patients with cancer. Oncology drug shortages often result in disruptions in the timing of chemotherapy treatments, alterations in the dose or regimen administered, or even missed doses when alternative agents are unavailable. The purpose of this survey was to characterize the impact of oncology drug shortages across the United States, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…A study on the impact of COVID-19 on global drug shortages emphasized a similar aspect [ 25 ]. Studies in the US also highlighted the increase in medicine shortages during the pandemic [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the impact of COVID-19 on global drug shortages emphasized a similar aspect [ 25 ]. Studies in the US also highlighted the increase in medicine shortages during the pandemic [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of proactive activities, even after well anticipation, financial constraints limit the procurement capacity, and only a few private setups or well-established NGO-based hospitals could be able to procure up to their need and for procuring more brands, only a few generics/brands are approved. For counteractive strategies, managing within hospitals leads to a change of protocol (rescheduled expensive treatment with or without compromised outcomes) [ 28 ], delayed treatment, and switching to alternatives (expensive second or third-line agents with less efficacy increased chances of medication error), all three would impact the optimum health outcomes to some extent [ 27 , 33 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fludarabine shortage is causing unease within the hematopoietic cell transplantation (HCT) and cell therapy community as most reduced intensity (RIC) platforms along with conditioning for engineered T cell products rely on fludarabine for lymphodepletion. A recent national survey drew attention to the significant impact of oncology drug shortages causing treatment delays and rising hospital costs [1]. Due to manufacturing delays, access to fludarabine specifically has been disproportionately affected in 2022.…”
Section: To the Editormentioning
confidence: 99%
“…As many anticancer drugs are only available as the generic version, the disruption within this supply chain has affected a substantial number of oncology patients worldwide. 8,9 This sector of the pharmaceutical industry relies heavily upon sourcing the main generic drug or active pharmaceutical ingredients from countries such as Asia, India and China. 2 Often termed as the 'production bottlenecks', any supply chain interruptions in these countries will have global consequences.…”
mentioning
confidence: 99%
“…In the United States, there has been an increase in clinical risk associated with prescribing alternative cancer treatment as a result of drug shortages. 9 A national survey completed by hospital oncology and haematology pharmacists reported that the prescribing of alternative agents has led to medication near-misses and errors (16% and 6%, respectively). 9 In the United Kingdom, in July 2022, 54% of pharmacists responding to a survey carried out by The Pharmaceutical Journal said that medicine shortages were now putting patient safety at risk.…”
mentioning
confidence: 99%